Trend in Household Expenditures in Albania - Ruzhdie Bici; Albana Hashorva (European Scientific Journal, ESJ, 2018)
In Albania almost 50% of the household expenditures go for food. The levels of the food have change by years but still have a considered weight in household budget. The study shows the trend and the significant factors that influence the food and non food consumption for different economic levels of the households in Albania. Household composition, geographic characteristics and other material deprivation dimensions have an important impact to the consumption trend and household wellbeing. The data refers to the Living Standard Measurement Survey (LSMS), which measure poverty through expenditures method. It is a multidimensional survey and gives us the possibility to have multi indicators and also disaggregate and test the relationship and influence. This paper shows the trend by household size, for different regions, the typology of the household and other socio-economic factors that may influence the food and non food expenditures trend. It is used the descriptive analyses and quintile regression of different foods level by different factors. The calculations are done using SPSS and Stata.